2010
DOI: 10.1007/s00415-010-5852-5
|View full text |Cite
|
Sign up to set email alerts
|

EEG low-resolution brain electromagnetic tomography (LORETA) in Huntington’s disease

Abstract: Previous studies have shown abnormal electroencephalography (EEG) in Huntington's disease (HD). The aim of the present investigation was to compare quantitatively analyzed EEGs of HD patients and controls by means of low-resolution brain electromagnetic tomography (LORETA). Further aims were to delineate the sensitivity and utility of EEG LORETA in the progression of HD, and to correlate parameters of cognitive and motor impairment with neurophysiological variables. In 55 HD patients and 55 controls a 3-min vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 80 publications
(138 reference statements)
2
35
1
Order By: Relevance
“…The results of EEG studies in HD and in animal models of HD imply the relevance of quantitative EEG characteristics as potential biomarkers of HD [22]. EEG abnormalities in HD patients consist of a marked reduction in alpha power and an increase in relative delta and beta power [23][24][25][26][27]. However, Hunter et al, (2010) found a trend toward higher global absolute alpha power in HD patients when compared to controls [28].…”
Section: Introductionmentioning
confidence: 98%
“…The results of EEG studies in HD and in animal models of HD imply the relevance of quantitative EEG characteristics as potential biomarkers of HD [22]. EEG abnormalities in HD patients consist of a marked reduction in alpha power and an increase in relative delta and beta power [23][24][25][26][27]. However, Hunter et al, (2010) found a trend toward higher global absolute alpha power in HD patients when compared to controls [28].…”
Section: Introductionmentioning
confidence: 98%
“…The empirical validity of LORETA has been established in a large number of studies [86] covering various EEG research fields, such as psychiatry [87,88], neurology [89,90], neuropsychopharmacology [91] and sleep medicine [92]. Further, the co-registration of LORETA with other neuroimaging methods has shown good correspondence of effects [93,94].…”
Section: Pharmaco-eeg – Advanced Topicsmentioning
confidence: 99%
“…The method was presented in the following articles: [9], [10], [11]. The article [1] presents one version of this method.…”
Section: Presentation Of the Problem And Proposed Solutionsmentioning
confidence: 99%